The current state of the labor market of the Republic of Kazakhstan and the analysis of problems arising in its regulation - Eskеndir, N.N.; Tattymbetova, К.Т.; Zhumasheva, A.B. (BUKETOV BUSINESS REVIEW, 2018)
The article is intended to assess the current state of the labor market in the country, in connection with the analysis of the macroeconomic indicators of the economy of the Republic of Kazakhstan for the years of independence, that is since 1991, uneven development and an increase in the positive dynamics of economic growth since 2000. After gaining independence, the labor market has undergone many changes. The level of economic activity of the population has increased, the number of employed in the economy has increased, the level of unemployment has decreased (especially among youth), the share of employed in the labor market has decreased in the structure of employment, real wage growth in the country, sector of economy, sector (public and private sector, formal and informal) changes in the structure of employment in this sector. Gradually, the role of small and medium-sized enterprises and services is gaining momentum in securing employment. The article also describes the level of economic activity in the labor market and its comparative indicators for the purpose of describing the overall situation in the labor market in the Republic of Kazakhstan. These analyzes revealed the problems that arise in the labor market and allowed to reveal the factors characterizing the current state of the labor market. The study showed that in different regions of Kazakhstan there are certain types of demographic features that are constantly growing in labor resources.